Journey through an alien world: portraying multi-layered nuances of patriarchy in K.R Meera’s Hangwoman - Mohanta, Subhasnata; Banerjee, Sutanuka (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper examines K.R. Meera’s novel Hangwoman (2015), translated into English from Meera (2012), originally written in Malayalam. The text unfolds the patriarchal domination over the social life of women in India. Although the title of the novel indicates it as the story of a female protagonist, her journey unfolds the multi-layered nuances of patriarchy at play in the sub-continental context. It investigates the blurring of boundaries and the constant negotiations between public and private spaces, both of which are controlled by powerful social institutions. Contemporary Indian literature, especially women’s writing, offers myriad perspectives of patriarchy that control women’s bodies and thoughts. This paper sheds light on the dominant forces of patriarchy in moulding the domestic as well as public worlds and also the cultural influences produced by such domination. The novel fictionalises the life of Chetna Gradha Mullick, the country’s first female executioner, and her journey through a typically male-dominated domain. It delves into how Chetna struggles to carve out a place for herself in the larger society while battling against patriarchal encroachment in her private life. Meera’s novel also portrays how violence and the possibility of violence constrain and control the actions of women under the present social order. The present paper involves a close textual and thematic analysis of the novel and also explores the feminist discourses on patriarchy to trace how the personal and public selves of women are constantly created and recreated through a complex process of negotiations with and resistance to the dominant power structures.